2023
DOI: 10.3389/fonc.2023.1115258
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for automatic head and neck lymph node level delineation provides expert-level accuracy

Abstract: BackgroundDeep learning-based head and neck lymph node level (HN_LNL) autodelineation is of high relevance to radiotherapy research and clinical treatment planning but still underinvestigated in academic literature. In particular, there is no publicly available open-source solution for large-scale autosegmentation of HN_LNL in the research setting.MethodsAn expert-delineated cohort of 35 planning CTs was used for training of an nnU-net 3D-fullres/2D-ensemble model for autosegmentation of 20 different HN_LNL. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Generally, few edits of the DLAS model contours were required. 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Wong et al found the commercial DLAS model that was used had worse performance (DSC, 0.72) compared with manual contouring, although the model led to fast contouring of CTV volumes. More data are needed to compare the performance of commercial and in-house DLAS models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, few edits of the DLAS model contours were required. 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Wong et al found the commercial DLAS model that was used had worse performance (DSC, 0.72) compared with manual contouring, although the model led to fast contouring of CTV volumes. More data are needed to compare the performance of commercial and in-house DLAS models.…”
Section: Resultsmentioning
confidence: 99%
“… 53 Weissman et al reported improved DLAS performance when the model was adjusted to the CT slice plane compared with when the model was not adjusted to the CT slice plane. 55 van der Veen et al reported best DLAS performance for LN levels Ib, II-IVa, VIa, VIb, VIIa, and VIIb (DSC, 0.85), and Kihara et al reported their DLAS model incorrectly segmented 1b lymph node levels for tonsillar and base of tongue cancer. 52 , 57 van der Veen et al also measured time to DLAS of all lymph node levels to be 86 seconds with the time needed to correct autosegmented contours of lymph nodes (35 minutes) to be less than time to correct manual contours (52 minutes).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the study illustrated diminishing returns as the training set size increased, with performance plateauing or even declining in some cases, a trend potentially attributed to the negative effects of inconsistent annotation in the authors’ data set. Similarly, Yu et al 13 and Weissmann et al 14 demonstrated that small, well-curated data sets can be used to train publicly available models to achieve clinically acceptable results.
Figure 3 Relatively small training sample sizes are needed to reach high geometric performance for deep learning auto-contouring models.
…”
Section: Insight 2: DL Auto-contouring Models Exhibit Reasonable Quan...mentioning
confidence: 99%
“…Automatic CT-based segmentation of these lymph node levels (e.g. I-V) is achievable and has been demonstrated by numerous works [10] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . Our clinic previously integrated a deep-learning based approach to contour elective lymph node levels in CT scans [10] .…”
Section: Introductionmentioning
confidence: 99%